2023
DOI: 10.1002/cphc.202300267
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Eigen or Zundel Features at Protonated Water Cluster–Aromatic Interfaces

Muthuramalingam Prakash,
K. Rudharachari Maiyelvaganan,
N. Giri Lakshman
et al.

Abstract: Interfacial interactions of protonated water clusters adsorbed at aromatic surfaces play an important role in biology, and in atmospheric, chemical and materials sciences. Here, we investigate the interaction of protonated water clusters ((H+H2O)n (where n=1–3)) with benzene (Bz), coronene (Cor) and dodecabenzocoronene (Dbc)). To study the structure, stability and spectral features of these complexes, computations are done using DFT‐PBE0(+D3) and SAPT0 methods. These interactions are probed by AIM electron den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Besides, this spectroscopy can be used to identify the excess proton localized in either the carbon surface or water clusters after comparison of the present spectra to those predicted recently for Bz–H + W n , Cor–H + W n and Dbc–H + W n ( n = 1–3) clusters. 66 Indeed, the presently computed UV-vis band wavelengths are significantly lower than those when the excess proton is localized at the water clusters.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Besides, this spectroscopy can be used to identify the excess proton localized in either the carbon surface or water clusters after comparison of the present spectra to those predicted recently for Bz–H + W n , Cor–H + W n and Dbc–H + W n ( n = 1–3) clusters. 66 Indeed, the presently computed UV-vis band wavelengths are significantly lower than those when the excess proton is localized at the water clusters.…”
Section: Discussionmentioning
confidence: 90%
“…For all species, we carry out computations at the PBE0/6-311++G** and PBE0-D3/6-311++G** levels, where D3 corresponds to the Grimme's dispersion correction to account for dispersion. 68 As established in the literature, 66,69 the PBE0-D3/6-311++G** level of theory is accurate enough to describe such protonated aromatic–water clusters since benchmarks revealed that PBE0-D3/6-311++G** competes with MP2/CBS and CCSD(T)/CBS, whereas a strong reduction in computational costs is noticed. In particular, we carried out additional MP2/6-311++G** calculations for BzH + –W n ( n = 1–3) clusters.…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations